Strategies to develop vaccines of pediatric interest - Susanna Esposito; Nicola Principi (Expert Review of Vaccines, 2017)
Introduction: The success of the vaccines available on the market has significantly increased interest in vaccine development. Areas covered: The main aim of this paper is to discuss the most important vaccines of pediatric interest that are currently being developed. New pneumococcal vaccines and vaccines against group B Streptococcus, Staphylococcus aureus and respiratory syncytial virus are analyzed in detail. Expert commentary: Advances in understanding human immunology, including human monoclonal antibody identification, sequencing technology, and the ability to solve atomic level structures of vaccine targets have provided tools to guide the rational design of future vaccines. It is likely that some of these vaccines will reach the market in the future and will thus partially contribute to the prevention of very severe diseases that significantly affect the morbidity and mortality of children. However, further studies in animals and several clinical trials in children must be performed before new vaccines become licensed.